2018
DOI: 10.1002/ccr3.1468
|View full text |Cite
|
Sign up to set email alerts
|

Life threatening nontraumatic tension gastrothorax

Abstract: Key Clinical MessageTension gastrothorax is a rare condition, which poses a diagnostic dilemma and can be mistaken for a tension pneumothorax. Awareness of the risk factors, clinical presentation, and radiology findings of tension gastrothorax can help with the prompt identification and successful management of this life‐threatening condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Management algorithm for the management of tension gastrothorax had been earlier recommended 6. Options for decompression include insertion of wide-bore nasogastic tube,8 needle thoracostomy,5 percutaneous aspiration,7 endoscopic decompression,9 10 emergency laparotomy and emergency thoracotomy 5. While needle thoracostomy is almost always successful in decompressing tension pneumothorax, it is successful in decompressing tension gastrothorax in only 9% of the patients 6.…”
Section: Discussionmentioning
confidence: 99%
“…Management algorithm for the management of tension gastrothorax had been earlier recommended 6. Options for decompression include insertion of wide-bore nasogastic tube,8 needle thoracostomy,5 percutaneous aspiration,7 endoscopic decompression,9 10 emergency laparotomy and emergency thoracotomy 5. While needle thoracostomy is almost always successful in decompressing tension pneumothorax, it is successful in decompressing tension gastrothorax in only 9% of the patients 6.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all reports of tension gastrothorax describe patients in shock or cardiopulmonary arrest who were diagnosed by CT imaging and attempted to decompress with a gastric tube. [8][9][10] Shoji et al 10 authored the eight previously reported cases, and only two cases involved hiatal hernia without trauma. In all of these reports, insertion of a gastric tube was attempted; however, in some cases, the insertion was unsuccessful and return of spontaneous circulation was achieved with volume resuscitation and cardiopulmonary resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure owing to the esophageal hiatal hernia displacing the heart 6,7 and tension gastrothorax in patients with obstructive shock due to a significant displacement of the heart by an expanded stomach have also been reported. Interestingly, all reports of tension gastrothorax describe patients in shock or cardiopulmonary arrest who were diagnosed by CT imaging and attempted to decompress with a gastric tube 8–10 . Shoji et al 10 .…”
Section: Discussionmentioning
confidence: 99%